Kajian Tematik tentang Malaikat - Azibur Rahman; Wahyu Aditama (FIRDAUS, 2024)
In the study of moral beliefs, knowing angels is the second thing that is usually explained by scholars after introducing the chapter on moral beliefs to Allah Ta'ala. By nature, angels are creatures that are invisible or supernatural. So, the first capital in knowing angels is to believe in them, which is part of the pillars of faith of Muslims. The aim of this research is of course for us to know and recognize angels from the source of the Koran and the interpretations of interpretive scholars. By knowing angels, a Muslim's faith increases and can also motivate a Muslim to always do good deeds. This writing method uses literature study, which the author took from various journals and books of interpretation. Of the many verses about angels, the author includes the first verse in the composition of the Al-Quran manuscripts which explains angels. To sharpen it, he added verses about other angels. Various tasks are mandated by Allah Ta'ala to angels, such as chanting tahmid, tasbih and so on. So, there is also one of the characteristics of angels that Allah Ta'ala created that can influence humans so that they tend to do good. Keywords : Angel, Interpretation, Thematic, Belief, Morality